2006
DOI: 10.1038/modpathol.3800561
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of loss of heterozygosity in intestinal- and solid-type gastric carcinomas: a comprehensive study using the crypt isolation technique

Abstract: The clinicopathological significance of loss of heterozygosity (LOH) in gastric carcinoma remains poorly understood. We and other researchers have previously demonstrated that LOH is fairly common in intestinaland solid-type gastric carcinomas, but rare in diffuse-type tumors. In this study, we investigated the relationship between clinicopathological variables and LOH status in intestinal-and solid-type gastric carcinomas. The crypt isolation technique was utilized to analyze LOH at 1p36, 3p14, 4p15, 5q21-22,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…13 The latter resides in the long arm of chromosome 9 that is frequently deleted in human cancers. 14, 15, 16 This prompted us to investigate whether the deletion of that region caused miR-204 downregulation in gastric tumoral tissues. To this end, we evaluated the presence of TRPM3 gene loss using a PCR-based test termed Multiplex Ligation-dependent Probe Amplification.…”
Section: Resultsmentioning
confidence: 99%
“…13 The latter resides in the long arm of chromosome 9 that is frequently deleted in human cancers. 14, 15, 16 This prompted us to investigate whether the deletion of that region caused miR-204 downregulation in gastric tumoral tissues. To this end, we evaluated the presence of TRPM3 gene loss using a PCR-based test termed Multiplex Ligation-dependent Probe Amplification.…”
Section: Resultsmentioning
confidence: 99%
“…are frequent in gastric adenocarcinomas [16][17][18][19]. Some further studies have shown that DNA deletions at chromosome position 5q21-22 are common in GCs [12,20,21], which is also the chromosome locus of APC. Inactivation of APC in GCs might be also attributed to CNV of the gene.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate levels of wild-type APC are critical to cytoskeletal integrity [1,6], cellular adhesion [7] and Wingless/Wnt signalling [5,8,9]. Somatic mutations of APC are common in gastrointestinal cancers [10][11][12]. Truncation of APC results in the disruption of complex formation and ultimately increased cytoplasmic levels of ß-catenin, which up-regulates TCFresponsive genes critical for the proliferation and transformation of epithelial cells of the gastrointestinal tract [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Solid‐type PDA seems to correspond to solid carcinoma, which is a poorly differentiated variant of tubular adenocarcinoma in the WHO classification . Solid carcinoma is similar to intestinal‐type GC in molecular features . Nonsolid‐type PDA and signet‐ring cell carcinoma correspond to diffuse‐type GC in Lauren’s classification or poorly cohesive carcinoma in the WHO classification…”
Section: Discussionmentioning
confidence: 99%
“…38 Solid carcinoma is similar to intestinal-type GC in molecular features. 39 Nonsolid-type PDA and signet-ring cell carcinoma correspond to diffuse-type GC in Lauren's classification 40 or poorly cohesive carcinoma in the WHO classification. 38 According to The Cancer Genome Atlas, diffuse-type morphology is associated with GS, which is one of the molecular subtypes of GC.…”
Section: F I G U R Ementioning
confidence: 99%